1223. In Vitro Activity of Ceftazidime-Avibactam and Comparator Agents Against Enterobacterales from ICU and Non-ICU Wards Collected in Latin America and Globally as part of the ATLAS Surveillance Program 2017-2019. (4th December 2021) - Lob, Sibylle; Hackel, Meredith; Stone, Gregory; Sahm, Daniel F
Abstract: Background: Ceftazidime-avibactam (CAZ-AVI) is a β-lactam/non-β-lactam β-lactamase inhibitor combination with activity against Enterobacterales producing class A, C and some class D β-lactamases. Resistance caused by these β-lactamases is especially high in ICUs. This study evaluated the in vitro activity of CAZ-AVI and comparators against Enterobacterales isolates from patients in ICU and non-ICU wards. Methods: Non-duplicate clinical isolates were collected in 2017-2019 from patients in Asia/Pacific, Europe, Latin America, and Middle East/Africa. Susceptibility testing was performed using CLSI broth microdilution and interpreted using CLSI 2021 and FDA (tigecycline) breakpoints. PCR and sequencing were used to determine the β-lactamase genes present in all isolates with meropenem (MEM) MIC >1 µg/ml, and Escherichia coli, Klebsiella spp. and Proteus mirabilis with aztreonam or ceftazidime MIC >1 µg/ml. Results: The activity of CAZ-AVI and comparators is shown in the table. Susceptibility rates among global Enterobacterales were generally lower for isolates from patients in ICU than non-ICU wards, but this difference was small for CAZ-AVI, which inhibited >96% of isolates from both ward types. Among MEM-nonsusceptible (NS) isolates, CAZ-AVI was active against 62.3% and 65.6% of ICU and non-ICU isolates, respectively, and 36.3% and 33.2%, respectively, carried metallo-β-lactamases (MBLs). CAZ-AVI inhibited >97% of MEM-NS MBL-negative isolates collected globally. Antimicrobial activity against all Enterobacterales from both ICU and non-ICU wards in Latin America (LA) was generally similar to the global average. Among MEM-NS isolates, antimicrobial activity of CAZ-AVI was >10 percentage points higher in LA than the global average among isolates from both ward types, at least partly because of a lower proportion of MBL-positive isolates in this subset (24.4% and 22.0% in ICU and non-ICUs, respectively). CAZ-AVI inhibited >98% of MEM-NS MBL-negative isolates from LA. Results Table Conclusion: CAZ-AVI provides a valuable treatment option for infections caused by Enterobacterales that do not carry MBLs, including those from patients in ICU wards, where antimicrobial resistance is typically higher. Disclosures: Sibylle Lob, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Gregory Stone, PhD, AztraZeneca (Shareholder, Former Employee)Pfizer, Inc. (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)